Conductive 2D Metal‐organic Framework (Co, NiCo, Ni) Nanosheets for Enhanced Non‐enzymatic Detection of Urea. Issue 6 (6th April 2021) - Wang, Xiaoya; Liu, Bingbing; Li, Jie; Zhai, Yunyun; Liu, Haiqing; Li, Lei; Wen, Herui
Abstract: 2D metal‐organic framework (MOF) has potential applications in electrocatalysis owing to fast mass transfer, charge transfer and large specific surface area. Here, we had prepared three conductive 2D MOF based on Ni, NiCo and Co in a simple and rapid way. The 2D nanostructure of MOF was confirmed by SEM and TEM. The chemical composition was studied by XRD, Raman and XPS spectrum. The electrochemical oxidation and detection was investigated through cyclic voltammetry and current‐time method. Their sensing performance for urea was determined by varying oxidation potentials and metal sites. The non‐enzymatic Ni‐, NiCo‐ and Co‐MOF sensors had good catalytic activity for urea. Compared with NiCo‐ and Co‐MOF, Ni‐MOF had a wider linear range (0.5–832.5 μM), high sensitivity (1960 μA mM −1 cm −2 ), low detection limit (0.471 μM), and fast response time. The sensors had well repeatability, reproducibility, and selectivity to specific interfering species. Furthermore, Ni‐ and NiCo‐MOF modified electrode was also applied to detection of milk samples. The results showed that the recovery was satisfactory, which further confirmed the effectiveness of non‐enzyme sensor. In general, the highly‐sensitive 2D Ni‐ and NiCo‐MOF modified electrode has great potential as nonenzymatic urea sensors for real samples detection in hydrogen energy, clinical diagnostics, and environmental protection, et al. Abstract :